Method for producing hydraulic adhesive

By introducing aluminum sources, ion sources and counter-ion sources in the production process of hydraulic adhesives, aluminum hydroxide is converted into crystalline AFt phase and converted into AFm phase, the problem of environmental sustainability and performance of Portland cement is solved, and environmentally friendly, high-performance and fast solidified hydraulic adhesives are achieved.

CN119677703APending Publication Date: 2025-03-21ECOSCITEC INNOVATIONS PTY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380058609.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-17
Filing Date
2023-07-28
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The production process of existing Portland cement requires a large amount of energy and its environmental sustainability is questioned, especially due to the significant decline in hydration products over a relatively short period of time.

Method used

By introducing an aluminum source, ion source and counter-ion source, aluminum hydroxide is converted into a crystalline AFt phase and driven by dehydration of the water body to convert it into a crystalline AFm phase, thereby forming an environmentally friendly hydraulic adhesive.

Benefits of technology

This method not only reduces carbon emissions, improves the mechanical properties and environmental stability of the hydraulic adhesive, but also significantly shortens the solidification time of the hydraulic adhesive to achieve a higher strength of 28 days.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677703A_ABST
    Figure CN119677703A_ABST
Patent Text Reader

Abstract

A method for producing a hydraulic binder comprising: introducing an aluminum source into a body of water to produce aluminum hydroxide; introducing an ion source in the form of slag into the body of water, the ion source configured to release a plurality of ions to the body of water; introducing a counter ion source into the body of water, the counter ion source configured to release a plurality of counter ions to the body of water; converting at least a portion of the aluminum hydroxide, at least a portion of the plurality of counter ions, and / or at least a portion of the plurality of ions to a crystalline AFt phase; and converting at least a portion of the crystalline AFt phase to a crystalline AFm phase using at least a portion of the plurality of ions, wherein the crystalline AFm phase and / or the crystalline AFt phase form the hydraulic binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a hydraulic binder. In particular, the present invention relates to a hydraulic binder produced by an improved cement hydration mechanism. Background Art

[0002] Portland cement is the most common type of hydraulic binder used throughout the world and is the basic ingredient in concrete, mortar, plaster, and non-specialty grouting. Portland cement's widespread use is due, at least in part, to the low cost and ready availability of the materials from which it is made.

[0003] However, the continued and expanded use of Portland cement has been questioned recently due to the high energy requirements of its production process. In addition, the production of each ton of Portland cement clinker produces an average of 843 kg of carbon dioxide, which has raised concerns about the environmental sustainability of the product.

[0004] An important step in the utilization of Portland cement is the hydration step. Portland cement powder is dissolved in water and produces hydration products in the form of calcium hydroxide (CH) and calcium silicate hydrate (CSH) at a pH of about 13.5. Like calcium hydroxide (CH), calcium silicate hydrate (CSH) not only has a variable composition, but also reacts with carbon dioxide and salts in the environment. This reaction with carbon dioxide and salts will destroy the stability of the hydration products, making CSH and CH no longer environmentally stable. Due to the reduction in stability, the properties of hydrated Portland cement will significantly decrease in a relatively short period of time (due to decomposition).

[0005] Several attempts have been made to overcome the drawbacks of the CO2 burden. For example, alternative hydraulic binders such as geopolymer cements (which typically combine aluminum silicates with chemical activators) have been used as a more environmentally friendly alternative to Portland cement. However, these geopolymer cements tend to have inferior mechanical properties to Portland cement and are prone to higher degradation rates due to the accelerated decomposition mechanism caused by residues from the geopolymer activation process.

[0006] In view of the above, it would be advantageous to provide an improved hydraulic binder and method for making the same, so that the product has better mechanical properties and environmental stability while being more environmentally friendly than Portland cement.

[0007] It should be clearly appreciated that, if a prior art publication is referred to herein, this reference does not constitute an admission that the publication forms part of the common general knowledge in Australia or any other country. Summary of the invention

[0008] Embodiments of the present invention provide a method for producing a hydraulic binder that may at least partially address one or more of the above-mentioned problems or deficiencies, or may provide the public with a useful or commercial choice.

[0009] According to a first aspect of the present invention, there is provided a method for producing a hydraulic binder, comprising:

[0010] introducing an aluminum source into a body of water to produce aluminum hydroxide;

[0011] introducing an ion source in the form of slag into the body of water, the ion source configured to release a plurality of ions into the body of water;

[0012] introducing a counterion source into the body of water, the counterion source configured to release a plurality of counterions into the body of water;

[0013] converting at least a portion of the aluminum hydroxide, at least a portion of the plurality of counter ions, and / or at least a portion of the plurality of ions into a crystalline AFt phase; and

[0014] At least a portion of the crystalline AFt phase is converted into a crystalline AFm phase using at least a portion of the plurality of ions, wherein the crystalline AFm phase and / or the crystalline AFt phase forms the hydraulic binder.

[0015] It should be understood that the term "AFt phase" is an abbreviation for "aluminum oxide, iron oxide, tri-counter ion" or (Al2O3-Fe2O3-tri). The term represents a group of calcium sulfoaluminate hydrates. The general formula of the AFt phase is [Ca6(Al,Fe)(OH)6·12H2O]2·X3·nH2O, where X represents a charged anion (here X represents sulfate). Ettringite is a common member of the AFt group and is the name of the mineral supergroup to which all AFts belong.

[0016] It should be understood that the term "AFm phase" is an abbreviation for "aluminum oxide, iron oxide, mono-counter ion" or (Al2O3-Fe2O3-mono). It represents another group of calcium aluminate hydrates with the general formula [Ca2(Al,Fe)(OH)6]2·X·nH2O, where X represents an isolated anion. X can be one of a variety of anions, with common anions including hydroxyl, sulfate and carbonate.

[0017] It will be appreciated that the process of the present invention is carried out in the absence of Portland cement.

[0018] The aluminum source can be in any suitable form. For example, the aluminum source can include a single material, or can include two or more materials. Preferably, the aluminum source can be an inorganic material. More preferably, the aluminum source can include one or more water-soluble ionic compounds. The aluminum source can include one or more silicates, oxides, sulfates, sulfides (or other soluble sulfur-containing compounds), hydroxides, carbonates, chlorides, etc., or any suitable combination thereof. Therefore, it is envisioned that aluminum can introduce aluminum cations into the water body.

[0019] In some embodiments of the present invention, a calcium source can also be introduced into a water body. The calcium source can be in any suitable form. For example, the calcium source can include a single material, or can include two or more materials. Preferably, the aluminum source can be an inorganic material. More preferably, the calcium source can include one or more water-soluble ionic compounds. The calcium source can include one or more silicates, oxides, sulfates, sulfides (or other soluble sulfur-containing compounds), hydroxides, bromides, iodides, chlorides, acetates, etc., or any suitable combination thereof. Therefore, it is envisioned that calcium can introduce calcium cations into a water body.

[0020] It is envisioned that, in the present invention, depletion of pore solution calcium may drive the dissolution of the pozzolan material. Specifically, depletion of the solution at a relatively low pH (compared to conventional Portland cement processes) may extract ions from the raw materials introduced into the water body.

[0021] In some embodiments of the present invention, the aluminum source and the calcium source may include different compounds. Alternatively, the aluminum source and the calcium source may be the same compound. In this embodiment, the compound may be of any suitable type, such as, but not limited to, calcium aluminum silicate, calcium aluminum oxide, calcium aluminum halide, calcium aluminum hydroxide, calcium aluminum chloride, calcium aluminum sulfide, calcium aluminum sulfate, etc., or any suitable combination thereof.

[0022] As previously described, the ion source in the form of slag is introduced into the body of water. In a specific embodiment, the slag may include slag produced during steel manufacturing, such as slag produced in a basic oxygen furnace (BOF). Thus, the slag may be steel slag.

[0023] An estimated 190 to 280 million tons of steel slag is produced each year. Steel slag is considered a waste product, and an estimated 2 billion tons of it is landfilled worldwide. In some cases, rather than being sent to landfills, the slag is cast and compacted into road base material. However, the leaching of metals from the slag can result in toxic runoff, which can cause environmental problems.

[0024] By using steel slag as an ion source in the present invention, it is envisioned that a large amount of global waste can be used to produce an environmentally friendly hydraulic binder (using relatively low energy), the production of which can significantly reduce carbon emissions compared to conventional Portland cement production processes.

[0025] In some embodiments of the invention, the slag may be subjected to a size reduction process prior to introduction into the body of water. Any suitable size reduction technique may be used, such as, but not limited to, crushing, grinding, and the like.

[0026] The slag may be reduced to any suitable particle size. For example, the average particle size of the slag after the size reduction process may be less than 100 mm. In other embodiments of the invention, the average particle size of the slag after the size reduction process may be less than 50 mm. In other embodiments of the invention, the average particle size of the slag after the size reduction process may be less than 10 mm.

[0027] Preferably, the slag may be combined with calcium sulphoaluminate cement or calcium aluminate cement prior to introduction into the body of water. The slag may be subjected to a size reduction process prior to combination with calcium sulphoaluminate cement or calcium aluminate cement prior to introduction into the body of water.

[0028] The slag may be combined with the calcium sulfoaluminate cement or calcium aluminate cement in any suitable proportion. For example, the proportion of slag in the combined slag and calcium sulfoaluminate cement or calcium aluminate cement may be 1 wt % to 99 wt %. More preferably, the proportion of slag in the combined slag and calcium sulfoaluminate cement or calcium aluminate cement may be 10 wt % to 90 wt %. More preferably, the proportion of slag in the combined slag and calcium sulfoaluminate cement or calcium aluminate cement may be 25 wt % to 75 wt %.

[0029] In some embodiments of the present invention, the ion source may include an aluminum ion source. More preferably, the ion source may include an aluminum ion source and a calcium ion source. More preferably, the ion source may include an aluminum ion source, a calcium ion source and a silicon ion source. However, it is envisioned that the slag may constitute an ion source of some other elements, such as but not limited to gallium, manganese, tungsten, cadmium, chromium, strontium, cobalt, lead, nickel, barium, titanium, molybdenum, vanadium, selenium, arsenic, iodine, bromine, boron, chlorine, etc. Therefore, in the present invention, the slag does not constitute a conventional gelling agent, but a "minable" resource, because ions can be recovered from the slag for the method of the present invention. It is envisioned that in the method of the present invention, ions of other elements can be used to help form the AFt phase.

[0030] It is expected that in conventional processes, ions of other elements are not normally utilized because they are not normally present in the water column at the start of hydration and / or are inhibited by their reaction rate or are excluded by more reactive / more dominant ions. However, the introduction of these ions into the water column before the normal hydration reaction occurs can result in phase reactivity and a relatively small effect of particle size on hydration rate compared to processes using Portland cement.

[0031] It will be appreciated that slags such as steel slag are classified as having low reactivity. However, the reactions occurring in the process of the invention are generally rapid (certainly faster than in the hydration of Portland cement), even if the slag is not ground to a relatively small particle size.

[0032] In particular, it is envisioned that the present invention may include a series of reactions in which one or more products of a prior reaction may be utilized. Thus, in some embodiments, the sequence of reactions may include a stepwise reaction sequence.

[0033] When the soluble ion content of the water becomes low, the reaction sequence can drive (or be manipulated to drive) a process whereby less favorable ions (in terms of their reactivity or crystal forming properties) can be liberated or scavenged from the ion source. Thus, phases of the ion source that may have low reactivity can be effectively mined from the ion source to provide solutes for the formation of other members of the solid solution series. For example, silicate counterions can be extracted from the C2S phase before normal hydration occurs, before forming the more stable but slower-forming C2S phase. Atmospheric carbon dioxide is captured as a counter ion in the process of forming a solid solution member rather than a faster forming solid solution member of the ettringite (C6ASSS) series, the latter of which decomposes to calcium carbonate, aluminum hydroxide and calcium sulfate in the presence of atmospheric carbon dioxide.

[0034] The counterion source can be in any suitable form and can release the counterion to the water body in any suitable manner, for example by dissolving in the water body. However, preferably, the counterion source may include one or more water-soluble inorganic compounds. In this embodiment, the counterion can be released into the water body by the dissociation of the water-soluble inorganic compound. It is understood that the exact nature of the counterion source depends on the counterion to be released into the water body. For example, if the desired positive counterion includes sodium, the counterion source may include a water-soluble sodium compound (such as sodium chloride, sodium oxide, sodium sulfate, sodium carbonate, sodium hydroxide, etc., or any suitable combination thereof). In some embodiments, the desired counterion may include sodium, potassium, calcium, iron, aluminum, copper, nickel, strontium, chromium, zinc ions, etc., or any suitable combination thereof. In a most preferred embodiment, the counterion source may include a calcium ion source. In a preferred embodiment of the present invention, a stoichiometric excess of calcium ions may be provided to drive the formation of a crystalline AFt phase.

[0035] The negative counterions provided by the counterion source may be in any suitable form, and it will be appreciated that the negative counterions may vary depending on the nature of the positive counterions, the nature of the aluminum source (and calcium source, if present), etc. Thus, it is envisioned that the negative counterions may include carbonate anions, chloride anions, oxide anions, sulfate anions, hydroxide anions, etc., or any suitable combination thereof.

[0036] The water body can be any suitable type, and it is understood that the size and properties of the water body will depend on the amount of the crystalline AFt phase to be produced. However, preferably, the water body includes a pool, a vat, a tank, a pond, a reservoir, etc. Although the water in the water body can be in any suitable form, before adopting the method of the present invention, it is preferably relatively ion-free water. However, in some embodiments of the present invention, a certain amount of counter ions can be included in the water. Although water can have any suitable pH, preferably, water can have a relatively neutral pH, or a slightly alkaline pH (i.e., pH is 7 to about 9).

[0037] In some embodiments of the invention, one or more reactants may be added to the water body. The one or more reactants may be in any suitable form, and those skilled in the art will appreciate that the addition of the one or more reactants (and the amount of the one or more reactants) will depend on the properties and composition of the other components in the method, etc.

[0038] In certain embodiments of the present invention, one or more reactants may include one or more of a plasticizer, a retarder and an accelerator. Any suitable substance may be used as a plasticizer, a retarder and an accelerator. However, in one embodiment of the present invention, the plasticizer may include calcium naphthalenesulfonate. In one embodiment, the retarder may include an acid, particularly citric acid. In one embodiment, the accelerator may include lithium carbonate, particularly relatively fine lithium carbonate.

[0039] It is envisioned that the aluminum hydroxide produced from the aluminum source can be produced in any suitable manner. However, preferably, the aluminum hydroxide can be produced as a precipitate. More specifically, the aluminum hydroxide can be precipitated as an aluminum hydroxide gel. By further explanation, it is envisioned that the aluminum hydroxide formed precipitates from the solution in the form of an amorphous semi-soluble polymer and then combines with calcium to form a hydrated ion pair. The formation of this ion pair is the reason why the AFt phase grows as elongated needle-shaped crystals. Typically, there is a water-insoluble catalyst at the bottom of the AFt crystal, which provides a charged surface on which the AFt is coordinated. The calcium-aluminum ion pair is further inserted into the bottom of the crystal, effectively pushing or growing the crystal from the bottom.

[0040] Any suitable reaction can be used to precipitate aluminum hydroxide from solution. A specific example of an aluminum hydroxide precipitation reaction (involving aluminum chloride, sodium carbonate and water) is as follows:

[0041] 2AlCl3+3Na2CO3+3H2O→2Al(OH)3+3CO2+6NaCl

[0042] Generally, the conversion of aluminum cations to aluminum hydroxide gel is relatively rapid. In addition, precipitation of aluminum hydroxide gel occurs at a pH of about 8, compared to the generation of CSH during conventional Portland cement hydration, which occurs at a pH of 13.5.

[0043] As previously described, at least a portion of the aluminum hydroxide, at least a portion of the ions, and at least a portion of the plurality of counterions are converted to a crystalline AFt phase. At least a portion of the aluminum hydroxide, at least a portion of the ions, and at least a portion of the plurality of counterions may be converted to any suitable crystalline AFt phase, but in a preferred embodiment of the invention, at least a portion of the aluminum hydroxide, at least a portion of the ions, and at least a portion of the plurality of counterions may be converted to ettringite. In this embodiment, the compound may be of the general formula:

[0044] (CaO)6(Al2O3)(SO3)3·32H2O

[0045] or

[0046] (CaO)3(Al2O3)(CaSO4)3·32H2O.

[0047] The aluminum hydroxide, at least a portion of the ions, and at least a portion of the plurality of counterions may be converted to the crystalline AFt phase by any suitable technique. However, preferably, the aluminum hydroxide, at least a portion of the ions, and at least a portion of the plurality of counterions are converted to the crystalline AFt phase by a hydration mechanism. It is envisioned that the crystalline AFt phase may absorb a relatively large amount of water from a body of water, thereby causing the crystalline AFt phase to have a relatively high water content.

[0048] The crystalline AFt phase may have any suitable crystal structure. For example, the crystalline AFt phase may have a triangular, monoclinic, orthorhombic, tetragonal, trigonal, hexagonal or cubic crystal structure, or any suitable combination thereof. However, preferably, the crystalline AFt phase has a relatively elongated (or needle-like) morphology. Preferably, the crystalline AFt phase has a relatively high water content.

[0049] As previously described, at least a portion of the crystalline AFt phase is converted to a crystalline AFm phase. This can be achieved by any suitable technique. However, in a preferred embodiment of the present invention, it is envisioned that the conversion of the crystalline AFt phase to the crystalline AFm phase is at least partially driven by the dehydration of water during the formation of the crystalline AFt phase. More specifically, as water is consumed during the formation of the crystalline AFt phase, a reduction in available water facilitates the conversion of the crystalline AFt phase to the crystalline AFm phase.

[0050] As mentioned above, the transformation of the crystalline AFt phase to the crystalline AFm phase is carried out in the presence of an ion source. In a preferred embodiment of the present invention, an ion source may be provided to drive the formation of the crystalline AFt phase and / or the crystalline AFm phase.

[0051] In conventional processes, environmental substances (such as salts, carbon dioxide, etc.) may be attracted to the process and may react to degrade or decompose the reaction products. However, in the present invention, not only do the reaction products (crystalline AFt phase and crystalline AFm phase) not react substantially with environmental substances, but environmental substances may also react to facilitate the formation of crystalline AFt phase and / or crystalline AFm phase. Therefore, environmental substances not only do not have a detrimental effect on the present invention, but may also increase the formation of crystalline AFt phase and / or crystalline AFm phase.

[0052] The crystalline AFm phase may be in any suitable form. In a preferred embodiment of the invention, the crystalline AFm phase may comprise a combination of monocarbonate, monosulfate and gehlenite hydrate (C2ASH8).

[0053] It is envisioned that the crystalline AFt phase may be a rapidly forming, thermodynamically unstable crystalline hydrate. The crystalline AFt phase may include an elongated morphology and may have a relatively high water content. However, it is envisioned that the crystalline AFt phase may form a dispersed, discontinuous support structure that preferably defines the initial size of the cement product, especially the size of the cement product after solidification.

[0054] Therefore, it can be envisioned that the crystalline AFt phase can form a framework structure or scaffold, on which the crystalline AFm phase can form.

[0055] As previously mentioned, it is contemplated that the formation of the crystalline AFt phase may consume significant amounts of water. Thus, hydration of the crystalline AFt phase facilitates the conversion of at least a portion of the crystalline AFt phase by dehydrating unbound pore water to a point where the unavailability of water in the water column slows or stops the formation of the crystalline AFt phase, thereby shifting the reaction to the formation of the crystalline AFm phase. The formation mechanism of the crystalline AFm phase may include sequential substitution of elements in the crystalline AFt phase and / or counterions.

[0056] In some embodiments, the formation of a crystalline AFm phase may occur within a framework or scaffold of a crystalline AFt phase. It is envisioned that the formation of a continuous crystalline matrix within the AFt framework structure may subject the AFt framework structure to dehydration conditions. This, in turn, may destabilize the AFt framework structure, causing the AFt crystals to decompose into their base materials, thereby making them available for consumption by the ongoing AFm hydration process.

[0057] The crystalline AFm phase can have any suitable crystal structure. For example, the crystalline AFm phase can have a trigonal, monoclinic, square, tetragonal, trigonal, hexagonal or cubic crystal structure, or any suitable combination thereof.

[0058] Essentially, the present invention utilizes an AFt-AFm conversion system to efficiently mine the components of a hydration mixture (i.e., the water body and the ion source therein), thereby allowing the use of non-reactive materials to form hydrates that have rapid strength growth and are stable in the environment.

[0059] As previously described, the hydraulic binder includes a crystalline AFm phase and / or a crystalline AFt phase. In some embodiments, the hydraulic binder may include both a crystalline AFm phase and a crystalline AFt phase. In other embodiments, the hydraulic binder may include only a crystalline AFm phase.

[0060] In some embodiments, the AFt phase and the AFm phase may include only a single crystalline form of AFt and AFm. In other embodiments of the present invention, the AFt phase and / or the AFm phase may include multiple crystalline forms of AFt and AFm. It is understood that different crystalline forms of the AFt phase and the AFm phase may have different crystalline structures, different chemical compositions and / or different stoichiometries from each other.

[0061] In some embodiments of the present invention, the hydraulic binder may further include one or more anhydrite deposits. More specifically, the hydraulic binder may further include one or more grape-like anhydrite deposits.

[0062] In a second aspect, the present invention resides broadly in a hydraulic binder formed by the method of the first aspect.

[0063] Advantageously, the present invention does not require the materials used to be gelling or hydraulic. Instead, the present invention only requires the formation mechanism of AFt hydrate, especially AFt hydrate crystals, and that the materials used have at least some solubility.

[0064] A further advantage of the present invention is that the initial pH is lower than that of conventional methods, and environmental substances (such as carbon dioxide, salts, etc.) attracted by the present method can be consumed as counter ions without causing decomposition or degradation of the hydration products.

[0065] Other advantages of the present invention include that the crystalline structure of the hydraulic binder reduces or eliminates shrinkage of the hydraulic binder. In addition, the fact that the hydraulic binder can be produced at a relatively weak alkaline pH not only makes the production process safer, but also reduces the amount of reagents required to produce the high alkaline pH associated with conventional Portland cement production.

[0066] In addition, the hydraulic binder of the present invention achieves strength very quickly compared to Portland cement. The rapid reaction rate of forming the hydraulic binder means that concrete formed using the hydraulic binder can achieve at least 25% of the total 28-day strength in less than about 4 hours from the initial setting, and 60% to 70% of the total 28-day strength can be achieved within 24 hours. In some embodiments, a further burst of hydration can occur 7 to 14 days from the initial setting. It is envisioned that the further burst of hydration may be associated with the silicates in the hydraulic binder.

[0067] Furthermore, the 28-day strength of the hydraulic binder prepared according to the method of the present invention is much higher (about 2-2.5 times higher) than the 28-day strength of conventional concrete formed using Portland cement.

[0068] The fact that the hydraulic binder of the present invention can achieve a high proportion of its total 28-day strength in a short period of time means that the hydraulic binder of the present invention can also be used in applications where conventional cement requires a longer period of time to set and cure before it can be used. For example, in 3D printing of a structure (such as a house, etc.), a first layer of a conventional cement product will be printed and then cured for a relatively long period of time to achieve a sufficient proportion of the 28-day strength before a second layer can be printed on the first layer.

[0069] In stark contrast, the rapid setting and curing of the hydraulic binder of the present invention means that a second layer can be printed on top of the first layer in a relatively short period of time after the first layer has been printed. Thus, the present invention increases overall construction speed and reduces structure construction time compared to conventional cement products.

[0070] Within the scope of the present invention, any feature described herein may be arbitrarily combined with any one or more other features described herein.

[0071] Reference to any prior art in this specification is not, and should not be taken as, an acknowledgment or any form of suggestion that the prior art is part of the common general knowledge.

[0072] Two Australian BOF slag samples (S500 and S502) were used to determine the efficiency of non-supersaturated reactions utilizing slag in a stepwise hydration mechanism. Specifically, the method was designed to demonstrate the stepwise reaction mechanism of the present invention and to exploit water transfer from AFt to AFm hydrates by modulating water availability during the hydration reaction. In this way, the hydration products can be shifted toward more environmentally stable natural compounds.

[0073] Slag S500 is of controlled composition and is taken from the top of the molten steel in the crucible. Slag S502 is the remainder of the formed slag and contains material that is discharged from the crucible during the steelmaking process. It contains a high proportion of steel particles and iron oxides.

[0074] Grouts containing various slags were formed, as well as a control grout without slag (ie, conventional CSA cement grout). The compositions of the grouts are shown in Table 1.

[0075] Slag slurry Control pulp Components weight% weight% Volcanic ash-slag 46.78 - Cement-CSA 23.39 23.39 Volcanic ash-calcium sulfate 7.80 7.80 Plasticizer-Calcium Naphthalenesulfonate 1.77 1.77 Retarder-citric acid 0.30 0.30 Accelerator-Lithium Carbonate 0.15 0.15 Sand-dry product 250-425μm 19.82 66.60

[0076] Table 1

[0077] Each slurry was then treated (the slag slurry was treated according to the method of the invention) to produce a hydraulic binder which was subsequently air-cured. The compressive strength of the hydraulic binder was tested for a period of 28 days. Table 2 lists the measured compressive strengths (in MPa).

[0078] aging S500 slag S502 slag Comparison 2 hours 0.00 0.00 0.00 4 hours - 18.95 6.41 6 hours 35.70 - - 1 day 39.82 - 31.19 2 days - 32.80 - 7 days 53.98 42.98 22.50 14 days - 56.71 - 21 days - 61.77 - 28 days 71.73 65.51 30.21

[0079] Table 2

[0080] The results listed in Table 2 show that the compressive strengths of the hydraulic binders produced according to the method of the present invention (ie, those produced from slag) are significantly higher than those of conventional Portland cement hydraulic binders.

[0081] Analysis of hydraulic binders produced from slags shows that the hydrate matrix consists of needle-like crystals forming a network. These crystals are ettringite crystals containing calcium aluminum and sulfate counterions. However, as hydration proceeds, the ettringite crystals are replaced by solid solution members of the ettringite family with mixed counterions.

[0082] In later stages, AFm hydrates and needle-shaped AFt crystals are present, and in some cases one or more anhydrite deposits (especially grape-like anhydrite deposits) appear.

[0083] Analysis of needle-shaped AFt crystals showed that its molecular formula is Ca3(Al n Fe 1-n )(OH)6(SO4,SiO4)xH2O, which is similar to the molecular formula of calcium sulfide silicate.

[0084] In summary, in the process of the present invention, the initial hydration produces an AFt hydrate based on a calcium aluminum framework with sulfate as the counter ion. The formation of ettringite rapidly consumes the ions and water content in the pore solution, prompting the AFt phase to absorb ions from other sources (including ion sources or slag). A portion of the crystalline AFt phase formed (in the form of ettringite) contains counter ions other than sulfate and forms a more stable AFt solid solution end member, such as woodfordite.

[0085] Subsequently, the crystalline AFt phase decomposes and reorganizes in sequence, resulting in a mechanistic change due to the limitation of the available water. The AFm hydrates initially formed were based on calcium, aluminum and sulfate as counter ions. However, with the decomposition of the more stable AFt phase containing ions other than sulfate, a series of AFm solid solution members began to form. At the same time, the anhydrous phase of the original component ion source (i.e., slag) and the counter ion source continuously put ions into solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0086] The preferred features, embodiments and variations of the present invention can be seen from the following detailed description, which provides sufficient information for those skilled in the art to implement the present invention. This detailed description should not be considered to limit the scope of the foregoing invention in any way. This detailed description will refer to the following figures:

[0087] Figure 1 A method for producing a hydraulic binder according to an embodiment of the present invention is shown.

[0088] Figure 2 A schematic diagram of a method for producing a hydraulic binder according to an embodiment of the present invention is shown. DETAILED DESCRIPTION

[0089] Figure 1 A method 10 for producing a hydraulic binder according to an embodiment of the present invention is shown. In this embodiment, an aluminum source 11 is introduced into a body of water 12. The aluminum source 11 is also a calcium source and may include any suitable soluble aluminum-calcium inorganic compound. In an embodiment of the present invention, the aluminum source 11 includes calcium suphoaluminate.

[0090] The dissociation of the inorganic compound including the aluminum source 11 in the water body causes a reaction between aluminum ions and water, resulting in the formation of aluminum hydroxide gel 13. The aluminum hydroxide gel 13 is produced at a pH of about 8, which is much less alkaline than the pH at which CSH gel is produced during the hydration of conventional Portland cement.

[0091] A source of counter ions 14 is also introduced into the body of water 12. Figure 1 In the embodiment of the present invention shown, the counter ion source 14 is a soluble inorganic calcium compound, such as calcium nitrate, calcium sulfate, calcium acetate, calcium hydroxide, calcium chloride, calcium bromide or calcium iodide, or any combination thereof. The dissociation of the inorganic compound of the counter ion source 14 introduces calcium cations and anions into the water body 12.

[0092] An ion source 16 in the form of BOF steel slag is also added to the body of water 12.

[0093] At least a portion of the aluminum hydroxide gel 13, at least a portion of the counter ions produced by the counter ion source 14, and at least a portion of the ions produced by the ion source 16 are then converted to the crystalline AFt phase. Figure 1 In the embodiment of the invention shown, the crystalline AFt phase is an AFt phase of ettringite 15. The composition of ettringite is (CaO)3(Al2O3)(CaSO4)3·32H2O.

[0094] The AFt phase of ettringite 15 is formed by a hydration mechanism of aluminum hydroxide gel 11, ions in ion source 16 and counter ions in counter ion source 14. It can be expected that the crystalline AFt phase can absorb a large amount of water from water body 12, so that the crystalline AFt phase 15 has a high water content. The AFt phase 15 of ettringite will have an elongated or needle-like crystal structure.

[0095] Ions (and especially calcium, aluminum and silicon ions) are extracted from the ion source 16 to drive the formation of the ettringite AFt phase 15. Thus, the slag used as the ion source 16 is effectively a "mineable" resource, as certain components of the slag can be extracted for use in the process of the present invention.

[0096] Environmental factors such as carbon dioxide 17 are generally considered harmful in conventional Portland cement hydration processes. However, in the process of the present invention, atmospheric carbon dioxide 17 can provide ions for converting aluminum hydroxide 13 into the AFt phase 15 of ettringite.

[0097] Since a certain amount of water 12 is absorbed during the hydration process to form the AFt phase 15 of ettringite, the reduction in available water 12 facilitates the transformation of the crystalline AFt phase 15 into the crystalline AFm phase 18. In some embodiments, the AFm phase may at least partially include gehlenite having the molecular formula C2ASH8.

[0098] exist Figure 1 In the embodiment, the formation mechanism of the crystalline AFm phase 18 includes the sequential replacement of elements and / or counterions 14 and / or ions 16 in the crystalline AFt phase 15.

[0099] The crystalline AFm phase 18 is formed within the framework structure or scaffold of the crystalline AFt phase 15. The formation of a continuous crystalline matrix within the AFt framework structure subjects the AFt framework structure to dehydration conditions. This, in turn, destabilizes the AFt framework structure, resulting in the decomposition of the AFt crystals 15 into their building blocks, making them available for consumption by the ongoing AFm hydration process.

[0100] AFm crystals 18 have the advantage of being environmentally stable, meaning that carbon dioxide 17 and salts 19 adsorbed during the hydration process do not react with the AFm crystals 18, so no decomposition or degradation of the AFm crystals 18 occurs (unlike the Portland cement hydration process).

[0101] Thus, the hydration product of the present invention is not only environmentally stable, but the crystal structure 18 of the AFm phase means that shrinkage of the AFm crystals 18 is reduced or eliminated, thereby providing a dimensionally stable product.

[0102] In addition, compared to the conventional Portland cement hydration process, the method 10 of the present invention is not only relatively fast, but the strength of the hydraulic binder (AFm crystals 18 and / or residual AFt crystals 15) also develops much faster than conventional Portland cement. In addition, the compressive strength of the hydraulic binder produced according to the method of the present invention is higher than that of conventional hydraulic binders produced using Portland cement. Specifically, the 28-day compressive strength of the hydraulic binder produced according to the method of the present invention is 2-2.5 times higher than the 28-day compressive strength of the conventional hydraulic binder produced using Portland cement.

[0103] Figure 2 A schematic diagram of a method 10 for producing a hydraulic binder 20 according to an embodiment of the present invention is shown. In the figure, counter ions 14 generated by a counter ion source and ions generated by a slag 16 react with an aluminum hydroxide gel 13 formed in a body of water 12 to form a crystalline AFt phase 15. As the reaction time (as shown by arrow 21) increases, the conversion of the counter ions 14 generated by the counter ion source, the ions generated by the slag 16, and the aluminum hydroxide gel 13 continues. This reaction corresponds to a reduction in free water in the system (as shown by arrow 22), which in turn drives the conversion of the crystalline AFt phase 15 to the crystalline AFm phase 18. The conversion of the crystalline AFt phase 15 to the crystalline AFm phase 18 is also driven by ions obtained from the slag 16 and carbon dioxide (such as carbon dioxide in the atmosphere).

[0104] As can be seen, the hydraulic binder 20 includes various forms of the crystalline AFm phase 18. It is envisioned that the hydraulic binder 20 may include the most chemically stable form of AFm.

[0105] exist Figure 2In the illustrated embodiment of the invention, the hydraulic binder 20 also includes a chemically stable AFt phase form 20a and one or more grape-like anhydrite deposits 20b.

[0106] In this specification and claims (if any), the word "comprising" and its derivatives, including "comprises" and "comprise", include each integer specified but do not exclude the inclusion of one or more other integers.

[0107] Reference throughout this specification to "one embodiment" or "an embodiment" means that the particular features, structures, or characteristics associated with that embodiment are included in at least one embodiment of the present invention. Therefore, the phrases "in one embodiment" or "in an embodiment" appearing in multiple places in this specification do not necessarily all refer to the same embodiment. In addition, the particular features, structures, or characteristics may be combined in any suitable manner into one or more combinations.

[0108] The present invention is described more or less in terms of specific structural or method features, depending on the statute. It should be understood that the present invention is not limited to the specific features shown or described, as the methods described herein include preferred forms of implementing the present invention. Therefore, the present invention is claimed in any form or modification thereof within the proper scope of the appended claims (if any) as properly interpreted by those skilled in the art.

Claims

1. A method for producing a hydraulic binder, comprising: introducing an aluminum source into a body of water to produce aluminum hydroxide; introducing an ion source in the form of slag into the body of water, the ion source configured to release a plurality of ions into the body of water; introducing a counter-ion source into the body of water, the counter-ion source configured to release a plurality of counter-ions into the body of water; converting at least a portion of the aluminum hydroxide, at least a portion of the plurality of counter ions, and / or at least a portion of the plurality of ions into a crystalline AFt phase; as well as At least a portion of the crystalline AFt phase is converted into a crystalline AFm phase using at least a portion of the plurality of ions, wherein the crystalline AFm phase and / or the crystalline AFt phase forms the hydraulic binder.

2. The method of claim 1, wherein a calcium source is also introduced into the body of water.

3. A method according to claim 1 or claim 2, wherein the aluminum source and the calcium source comprise one or more water-soluble ionic compounds.

4. The method of claim 3, wherein the one or more water-soluble ionic compounds comprise calcium aluminum silicate, calcium aluminum oxide, calcium aluminum halide, calcium aluminum hydroxide, calcium aluminum chloride, calcium aluminum sulfide, calcium aluminum sulfate, or a combination thereof.

5. A method according to any one of the preceding claims, wherein the source of counter ions comprises one or more water-soluble inorganic compounds.

6. The method of any one of the preceding claims, wherein the counter ion source is a sodium ion source, a potassium ion source, a calcium ion source, a iron ion source, a aluminum ion source, a copper ion source, a nickel ion source, a strontium ion source, a chromium ion source and / or a zinc ion source.

7. A method according to any one of the preceding claims, wherein the pH of the body of water is between 7 and 9.

8. The process according to any one of the preceding claims, wherein the aluminium hydroxide is produced in the form of a precipitated aluminium hydroxide gel.

9. The method of any one of the preceding claims, wherein at least a portion of the aluminum hydroxide and at least a portion of the plurality of counterions are converted to the crystalline AFt phase via a hydration mechanism.

10. The method according to any one of the preceding claims, wherein the crystalline AFt phase has a needle-like morphology.

11. The method according to any one of the preceding claims, wherein the crystalline AFt phase is in the form of an AFt phase of ettringite.

12. The method of any one of the preceding claims, wherein the slag comprises steel slag.

13. The method of claim 12, wherein the steel slag comprises BOF slag.

14. A method according to any one of the preceding claims, wherein the slag is subjected to a size reduction process prior to introduction into the body of water.

15. A method according to any one of the preceding claims, wherein the slag is combined with calcium sulphoaluminate cement or calcium aluminate cement prior to introduction into the body of water.

16. The method of any one of the preceding claims, wherein the crystalline AFm phase comprises a combination of monocarbonate, monosulfate and gehlenite hydrate.

17. A method according to any one of the preceding claims, wherein the crystalline AFm phase is formed by sequentially replacing the elements and / or the counter ions in the crystalline AFt phase.

18. A method according to any one of the preceding claims, wherein the crystalline AFt phase forms a framework structure or scaffold on which the crystalline AFm phase is formed.

19. The method of claim 17, wherein the formation of the crystalline AFm phase occurs within a framework structure or scaffold such that the framework structure or scaffold is subjected to dehydration conditions resulting in the decomposition of the AFt crystals into their base materials for consumption in the formation of the crystalline AFm phase.

20. The method of any one of the preceding claims, wherein the hydraulic binder further comprises one or more anhydrite precipitates.

21. A hydraulic binder formed according to the method of any one of the preceding claims.